2006
DOI: 10.1073/pnas.0608000103
|View full text |Cite
|
Sign up to set email alerts
|

Functional reconstitution and characterization of Pyrococcus furiosus RNase P

Abstract: RNase P, which catalyzes the magnesium-dependent 5-end maturation of tRNAs in all three domains of life, is composed of one essential RNA and a varying number of protein subunits depending on the source: at least one in bacteria, four in archaea, and nine in eukarya. To address why multiple protein subunits are needed for archaeal͞eukaryal RNase P catalysis, in contrast to their bacterial relative, in vitro reconstitution of these holoenzymes is a prerequisite. Using recombinant subunits, we have reconstituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
202
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 86 publications
(217 citation statements)
references
References 49 publications
14
202
0
1
Order By: Relevance
“…Reconstitution studies have revealed that the archaeal RNase P proteins function as two binary complexes: Pop5• Rpp30 and Rpp21•Rpp29 (23). Footprinting studies indicate that Pop5•Rpp30 interacts with the C domain, and Rpp21• Rpp29 interacts with the S domain of archaeal RNase P RNA (23,28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstitution studies have revealed that the archaeal RNase P proteins function as two binary complexes: Pop5• Rpp30 and Rpp21•Rpp29 (23). Footprinting studies indicate that Pop5•Rpp30 interacts with the C domain, and Rpp21• Rpp29 interacts with the S domain of archaeal RNase P RNA (23,28).…”
Section: Resultsmentioning
confidence: 99%
“…S4) with one surprising difference. All known bacterial and archaeal RNase P RNAs consist of both a substrate-specificity (S) domain that aids substrate recognition, and a catalytic (C) domain essential for phosphodiester cleavage (22,23). The Pyrobaculum RNase P RNA candidates have lost most of their S domain, but retain an intact C domain that includes all 11 universally conserved nucleotides (24) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This region is the high-affinity binding site of L7Ae in Pho RPR, and its absence in type M archaeal and all eukaryal RPRs suggests that a universal role for L7Ae and its homologs in RNase P catalysis must involve another RPR region. Therefore, we used a type M archaeal RNase P to investigate if L7Ae is indeed part of the holoenzyme and to understand how it influences catalysis.Using purified recombinant subunits, we and others have reconstituted type A and M RNase P from different thermophilic archaeal variants [Mth, Pho, Pyrococcus furiosus (Pfu) and Methanocaldococcus jannaschii (Mja)] (13,15,25,26). Because we expected studies on a mesophilic type M variant to yield results that are also applicable to eukaryal RNase P, we decided to focus on RNase P from Methanococcus maripaludis (Mma); this choice Author contributions: I-M.C…”
mentioning
confidence: 99%
“…Using purified recombinant subunits, we and others have reconstituted type A and M RNase P from different thermophilic archaeal variants [Mth, Pho, Pyrococcus furiosus (Pfu) and Methanocaldococcus jannaschii (Mja)] (13,15,25,26). Because we expected studies on a mesophilic type M variant to yield results that are also applicable to eukaryal RNase P, we decided to focus on RNase P from Methanococcus maripaludis (Mma); this choice was also inspired in part by the fact that transformation and homologous recombination are possible for Mma (27,28).…”
mentioning
confidence: 99%
“…First, reproducing the results of Kikovska et al (9) with different archaeal/eukaryal RPRs will bolster the idea that the catalytic core really rests with the RPR during evolution of RNase P. The corollary is that Rpps facilitate RPR catalysis by fine-tuning/stabilizing the active site for productive positioning of the substrate and catalytically important metal ions. Second, having conditions under which the human RPR is weakly active will permit an evaluation of the functional roles of individual human Rpps, as demonstrated for archaeal RNase P (15,16). Third, if eukaryal RPRs do form shortlived functional structures, cross-linking or RNA engineering could be attempted to trap these conformations and demonstrate that such RNAs could be weaned of their dependence on some Rpps.…”
mentioning
confidence: 99%